Survey of the initial management of celiac disease antibody tests by ordering physicians - Kathryn Potter; Lawrence de Koning; J. Decker Butzner; Dominica Gidrewicz (BMC, 2019)
Abstract Background Appropriate interpretation of a positive celiac antibody test by an ordering physician is important in order to institute proper management. We evaluated why children with an initial positive celiac serology were not referred for diagnostic biopsy or followed with serial testing by the ordering physician. Methods Consecutive celiac serologies in all patients less than 18 years of age were evaluated over 3.5 years and 775 children with a positive tissue transglutaminase antibody (TTG) were identified. If no management of a positive TTG could be identified, a survey was sent to the ordering physician. Responses were categorized as appropriate or inappropriate management. Results Of the 775 patients with a positive TTG, 193 (24.9%, 95% CI 21.9-28.1%) received no follow-up management. We contacted 173 ordering physicians and 120 (69%) responded. Of the 120 responses, 55 patients (45.8%, 95% CI 36.8-55.1%) were managed appropriately and 46 (38.3%, 95% CI 29.7-47.7%) were considered to be inappropriately managed when no repeat TTG was obtained within 18 months. Reasons for inappropriate management included: screen considered to be false positive (44.7%), patient was not experiencing symptoms of celiac disease (31.6%), symptoms had resolved (15.8%), results were not indicative of celiac disease (26.3%) and patients started a gluten-free diet with no evaluation of response (15.8%). In 19 patients the TTG was not acted upon for technical reasons. Conclusions Positive TTGs require appropriate interventions. These include: subspecialist referral for further evaluation and/or repeat testing to evaluate: 1) treatment response or 2) patients with minimal or no symptoms.